Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found